Pengaruh Pembayaran Non-Tunai Terhadap Kinerja Sektor Primer Di Indoensia - Mira Ayu Astari; Wisnu Wibowo (MediaTrend, 2022)
The purpose of this study is to examine the effect of non-cash payments on theperformance of the primary sector in Indonesia. The independent variables consistof ATM/Debit cards, credit cards, e-money, check payments, and RTGS payments.The dependent variable of the primary sector is divided into two, namely agricultural GDP and mining GDP. The data used is a secondary data type with time series, observation period 2010.q1-2019.q4. The analytical method of this study uses the Error Correction Model (ECM) estimation to determine the effect of non-cash payments in the short and long term. The short-term estimation results in the miningsector only have a significant influence on the RTGS variable, while in the long termit is influenced by credit cards, e-money, and RTGS. The results of the short-termestimation of the agricultural sector have a significant effect on credit cards, checks,and RTGS, while in the long term only checks are significant